RELATIVE SET GENERICITY (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2002)
A set of natural numbers is generic relatively a set $B$ if and only if it is the preimage of some set $A$ using a $B$-generic $B$-regular enumeration such that both $A$ and its complement are $e$-reducible to $B$.